UMP proudly produces 2,773 graduates in its 13th Convocation - UMP, PNC (2018)
Universiti Malaysia Pahang (UMP) will celebrate the graduation of 2,773 of its students in its 13th convocation ceremony to be held over two days on November 10 and 11 at UMP Gambang Campus Sports Complex.